Case Report: A rare case of primary hepatic paraganglioma: a mimicker of hepatocellular carcinoma - Li, Aitong; Ren, Silu; Yang, Xudan; Yang, Chong; Lu, Tao (Frontiers in Oncology, 2025)
Paragangliomas (PGLs) are pheochromocytomas outside the adrenal glands, most commonly found in the retroperitoneal space, head and neck, bladder, and mediastinum. However, PGL occurring in the liver are extremely rare. We present a case of a 70-year-old woman who presented to our hospital with right upper abdominal pain, persisting for 2 years. Abdominal contrast-enhanced computed tomography (CT) revealed a 3.8 x 2.7 cm hypervascular nodule in the caudate lobe of the liver, demonstrating arterial phase hyperenhancement and portal/delayed phase washout. Magnetic resonance imaging (MRI) further demonstrated diffusion restriction and low signal intensity in the hepatobiliary phase (HBP) of the nodule. Based on these imaging features, hepatocellular carcinoma (HCC) was initially diagnosed radiologically. Surgical resection was performed, and immunohistochemical staining revealed positivity for chromogranin A (CgA), synaptophysin (Syn), and S - 100 protein, confirming the diagnosis of primary hepatic PGL (HPGL). This case highlights that hypervascular lesions with washout and HBP hypointensity may mimic HCC. Pathological verification is crucial, especially in patients without typical HCC risk factors. Although exceedingly rare, HPGL should be considered in the differential diagnosis of hypervascular hepatic nodules demonstrating typical arterial phase hyperenhancement and portal/delayed washout on CT/MRI, particularly in female patients presenting with nonspecific symptoms and lacking typical HCC risk factors such as hepatitis, alcohol abuse, or elevated tumor markers.